Effect of preservation at refrigeration temperature on bacterial load and quality of buck semen - SIMON, LIZ; VIJAYAKUMARAN, V (The Indian Journal of Animal Reproduction, 2003)
The bacterial load in buck semen preserved under refrigeration temperature(8-12°C) was assessedby Pour Plate Method. The mean bacterial load showed an increasing trend from zero to 48 hours ofpreservation. However, there was no significant correlation between the bacterial load-and semenquality.
Keywords: Buck semen; refrigeration temperature; bacterial load